Descriptive analysis and comparison of strategic incremental rehearsal to "Business as Usual" sight-word instruction for an adult nonreader with intellectual disability. (2nd January 2018) - Richman, David M.; Grubb, Laura; Thompson, Samuel
ABSTRACT: Objective : Strategic Incremental Rehearsal (SIR) is an effective method for teaching sight-word acquisition, but has neither been evaluated for use in adults with an intellectual disability, nor directly compared to the ongoing instruction in the natural environment. Methods : Experimental analysis of sight word acquisition via an alternating treatment design was conducted with a 23-year-old woman with Down syndrome. SIR was compared to the current reading instruction (CRI) in a classroom for young adults with intellectual disabilities. CRI procedures included non-contingent praise, receptive touch prompts ("touch the word bat"), echoic prompts ("say bat"), textual prompts ("read the word"), and pre-determined introduction of new words. SIR procedures included textual prompts on flash cards, contingent praise, corrective feedback, and mastery-based introduction of new words. Results : The results indicated that SIR was associated with more rapid acquisition of sight words than CRI. Conclusion : Directions for future research could include systematic comparisons to other procedures, and evaluations of procedural permutations of SIR.